REJECTIVE BEHAVIOUR TOWARDS THE AFRICAN-AMERICAN CHARACTERS OF MATT RUFF’S LOVECRAFT COUNTRY NOVEL - Rozzan, Alya; Kuncara, Singgih Daru; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The study aims to identify the types of rejective behaviours portrayed in Matt Ruff’s Lovecraft Country novel and to discuss the portrayal of African-American characters’ responses to rejective behaviours. This research is a descriptive research that uses a mimetic approach and multicultural criticism to conduct the investigation. The data source of the study is Matt Ruff’s Lovecraft Country novel. The data are acquired from the narration and dialogues related to the mistreatments toward the African-American characters and their responses that are suitable to the criteria of Allport’s theory of rejective behaviours and Mellor’s responses to racism theory. The results show that verbal rejection (antilocution), discrimination, and physical attack are all portrayed in this novel albeit with different frequencies for each African-American character. It is also discovered that the characters have depicted defensive response, controlled response, and confrontational response in dealing with rejective behaviours.